1996
DOI: 10.1002/hep.510230112
|View full text |Cite
|
Sign up to set email alerts
|

Impaired bile flow and disordered hepatic calcium homeostasis are early features of halothane-induced liver injury in guinea pigs

Abstract: To characterize the early events in liver injury produced by halothane, experiments were performed in genetically susceptible guinea pigs 19 hours after halothane exposure. Serum bile acid concentrations were fourfold increased in halothane-exposed animals compared with controls. In isolated perfused liver experiments, livers from halothane-exposed animals did not differ in hepatic oxygen uptake or in perfusion pressure at the end of experiments, but bile flow and biliary bile salt concentrations were reduced.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Other studies have suggested that susceptible guinea pigs develop liver injury when they are exposed to halothane because they are more sensitive to hepatic ischemia ( , ), cholestasis (), and disturbances in calcium homeostasis ( , ) than resistant guinea pigs. Although our findings indicate that TFA-protein adducts are a contributing factor to the susceptibility of guinea pigs to halothane-induced liver injury, it remains to be determined whether they cause liver injury by initiating these or other pathological processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have suggested that susceptible guinea pigs develop liver injury when they are exposed to halothane because they are more sensitive to hepatic ischemia ( , ), cholestasis (), and disturbances in calcium homeostasis ( , ) than resistant guinea pigs. Although our findings indicate that TFA-protein adducts are a contributing factor to the susceptibility of guinea pigs to halothane-induced liver injury, it remains to be determined whether they cause liver injury by initiating these or other pathological processes.…”
Section: Discussionmentioning
confidence: 99%
“…Determination of the Extent of Liver Damage. Guinea pigs with serum ALT levels less than 2 times or greater than 5 times those of control animals, 48 h after halothane treatment, were classified as being either resistant or susceptible, respectively, to halothane-induced liver injury, as described previously ( , ). Animals with ALT that fell between these two limits were considered mildly susceptible.…”
Section: Methodsmentioning
confidence: 99%